Ghummeida: Outdoor Play in a Militarized Zone - Nadera Shalhoub-Kevorkian; Razzan Quran (Harvard FXB Center for Health and Human Rights, 2020)
This paper connects two seemingly distinct subjects-the right to health and children's play in contexts of a militarized settler colony. Following Ignacio Martín-Baró's articulation of a critical psychology "of the people," we outline the spatial and psychosocial economies of childhood outdoor play as forms of social and political determinants of health and human rights. We offer an analysis through the words and reflections of Palestinian Jerusalemite children that expose the mundane violence produced and sustained by the colonizer, whereby children's play creates spaces of livability against necropolitics. We draw on 50 observations of Palestinian children's play of Ghummeida-hide and seek-spanning 2020 through 2022 in four locations in occupied East Jerusalem. Our analysis proposes three overlapping fields through which Ghummeida operates: as a game, as resistance to spatial suffocation, and against unchilding. Across each of these fields, children's ways of embodying their right to play and live are presented as acts of refusing the chronic political violence they are exposed to. The produced processes include generativity, ownership of space, the surface and the body, and psychic repair. The paper concludes by unveiling how Ghummeida, with its metaphoric and embodied imprints, enables Palestinian children's psychosocial well-being, and pursuit of human rights, through defying their reality under a brutal system of apartheid.